Identification of Knowledge of Women of Childbearing Age On Examination of Visual Infection Acetic Acid (IVA) - Dede Mahdiyah; Dini Amalia; Susanti Suhartati (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Background: Cervical cancer is a disease caused by the growth of uncontrolled cervical epithelial cells. In Indonesia an estimated 15,000 new cases of cervical cancer occur each year, while the death rate is estimated at 7,500 cases per year where 40-45 new cases are found each day with the number of deaths reaching 20-25 people. Therefore, WHO states that Indonesia is among the countries with the highest incidence of cervical cancer in the world with 66% dying. The key to the healing of all types of cancer is early detection, one of them is with Visual Inspection of Acetic Acid.Purpose: identified the knowledge of Women of childbearing age (WUS) about examination of Visual Inspection of Acetic Acid (IVA) at Banjarmasin Indah Health Center.Methods: this research is descriptive research with population that is woman of childbearing age who visited in Poly Health Mother and Child (KIA) Banjarmasin Indah Health Center last three months. The sampling technique used is simple random sampling.Results: The results showed that respondents had plenty knowledge about the examination of visual inspection of acetic acid (63,08%), this result is evidenced by the number of women of childbearing age who are not screened or IVA examinations.Â Keywords: Knowledge, Visual infection of acetic acid, Women of childbearing age.